Evolution and impact of EU aid for food and nutrition security: A review - Lara Cockx; Nathalie Francken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
In the aftermath of the world food price crisis, the issue of food and nutrition security has received a high level of political attention and the international donor community has repeatedly underlined its commitment to combat hunger in the world. In order to enhance the effectiveness of the international community's efforts in addressing the widespread problem of malnutrition, we need to improve our knowledge on what activities donors are currently engaging in and which interventions have been shown to be successful. This paper offers both an overview of the aid for food and nutrition security landscape and how it has changed and an extensive review of the available evidence on the impact of a wide array of interventions aimed at addressing all four dimensions of food and nutrition security; availability, access, utilization and stability. We find that despite the renewed interest and elevated levels of funding for food and nutrition security assistance in developing countries, the empirical evidence base for the effectiveness of these interventions in improving beneficiaries' food and nutrition security - although in several cases promising - is weak. In particular, the question whether different interventions improve the quality of food consumption and consequently nutrient intake and status, remains largely unanswered. Moreover, few studies assess longer-term effects and there exists relatively little rigorous evidence that compares different interventions. It is therefore strongly recommended to undertake additional research to improve the evidence base as this would allow researchers and policy makers to establish the type of approaches that improve food and nutrition security in the most efficient and cost-effective manner. Finally, in order to facilitate this process, there is a need for a clear and uniform definition of food and nutrition security assistance on the one hand as well as agreed upon, comprehensive indicators on the other hand.
Keywords: F35; F53; I380; O12; O13; O15; 330; Nahrungsmittelhilfe; Ernährungssicherung; EU-Politik